A critical comparison on the origin of cosmos in Islam, Christianity and modern science - Amafua, Mahfuth Khamis (Department of Islamiyat, University of Peshawar, 2015)
People acknowledge the effort of Modern science in bringing cosmos into reality. The research made in space has made what was once considered impossible possible and has opened the cosmos wide for further investigations and discoveries. Modern western empirical science has surely been the most impressive intellectual development since the 16th century. But this cannot of course negate the role of religion which has been around for much longer than that and is still flourishing to date despite a sustained complain to stamp it out of human orbit. Hence, none can deny the contributions of theology represented by religion on the one hand, and that of modern science on the other, since time immemorial. Even though there are many important issues and questions in this discourse, this entry concentrates on just a few. Perhaps the most salient question is whether the relation between religion and science is characterized by conflict or by concord. Of course it is possible that there are conflict and concord, conflict along certain dimensions, concord along others. This is so because religion and science are definitive contemporary discussion of many issues surrounding our understanding of God and religious truth and experience in the scientific age. This is a significantly expanded and freshly revised version of Religion in an Age of Science. In order to narrow down the arguments the researcher deems it necessary to discuss only three parties highlighted in the above title. The main objective here is to accentuate the areas of agreement and disagreement in this regard, and find ways and means to harmonize theology and modern science for the betterment of the modern man. The researcher believes that despite the apparent contradictions between religion and science there are areas in which religious truths still needs to be validated if science is to be the yardstick of rationality based on reality.